The Effect of e-Wom And Brand Image on The Interest in Buying The Heavenly Blush Yoghurt Product - Muslih Mughoffar; Ujang Sumarwan; Netty Tinaprilla (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
The objectives of this research are: 1) to analyze the effect of e-WOM on brand image of Heavenly Blush product, 2) to analyze the effect of e-WOM on the interest in buying Heavenly Blush product, and 3) to analyze the effect of brand image on the interest in buying Heavenly Blush product. This research used online and offline survey methods in the form of questionnaires. The research sampling was carried out using non-probability sampling technique. The scaling technique of the study applied Likert scale which produces measurements at intervals; scale 1 for strongly disagree statements and scale 5 for strongly agree statements. The data analysis used PLS (Partial Least Square). The 106 respondents of the research were customers who already knew about Heavenly Blush yogurt products but had never consumed them with the minimum age of 17 years. The findings showed that there is a positive effect of e-WOM variable on brand image variable with a value of 0.425. The e-WOM variable has a positive effect on the interest in buying Heavenly Blush product with a value of 0.430. Brand image is the last variable that has a positive effect on interest in buying with a value of 0.244.Keywords: brand image, e-WOM, interest in buying, product, yogurt